2001
DOI: 10.1097/00005392-200102000-00023
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prostate Biopsy on Patient Well-Being: : A Prospective Study of Pain, Anxiety and Erectile Dysfunction

Abstract: The impact of prostate biopsy on patient well-being begins while waiting for the scheduled procedure. Shortening the anticipation period before results are disclosed and administering pre-biopsy anxiety decreasing measures may benefit patients. Analgesic therapy is recommended in younger patients, those reporting moderate to severe intraoperative pain and those with known prostatic inflammatory infiltrate. The risk of acute erectile dysfunction should be discussed cautiously with patients who are potent before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
181
4
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 15 publications
9
181
4
5
Order By: Relevance
“…4 Recently, there have been studies investigating urinary and erectile function after prostate biopsy. 2,3,5 There are few publications on preoperative and postoperative impact of serial prostate biopsies on active surveillance patients who ultimately undergo RARP. 5 This is especially relevant as one-third of men enrolled in AS may eventually require definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Recently, there have been studies investigating urinary and erectile function after prostate biopsy. 2,3,5 There are few publications on preoperative and postoperative impact of serial prostate biopsies on active surveillance patients who ultimately undergo RARP. 5 This is especially relevant as one-third of men enrolled in AS may eventually require definitive surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated a statistically significant difference between the prebiopsy IIEF-5 scores and postbiopsy scores at 1 and 6 months (Po0.001). The authors postulated that ED in their cohort could be attributed to The impact of multiple biopsies P Sooriakumaran et al direct neurovascular-bundle damage or secondary trauma such as nerve compression caused by hematoma or edema, a previous theory offered by Zisman et al 3 Studies by Akbal et al 11 investigated ED after saturation prostate biopsy. The median number of cores taken during prostate biopsy was 22 (range: 20--30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Nijs et al 42 reported that the idea of undergoing a prostate biopsy already caused anticipated pain and discomfort. Zisman et al 43 found that undergoing a prostate biopsy can have an impact on the patient's well-being due to causing pain and anxiety. Macefield et al 44 reported that although most men coped well with undergoing a biopsy, a minority experienced elevated distress at the time of biopsy and after receiving a negative result.…”
Section: Shared Decision Makingmentioning
confidence: 99%